PELATIHAN PEMANFAATAN AIR CUCIAN BERAS SEBAGAI PUPUK ORGANIK CAIR BAGI MASYARAKAT - Muhlis, Muhlis; Mustarin, Amirah; Puspitasari, Dewi; Danial, Mohamad Ikbal Riski A.; Diapati, Siti Maifa; Budiningtyas, Dwi Putri (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
In the soldiers' housing complex, a large volume of rice washing water is wasted, even though this waste can be used as a liquid organic fertilizer with high nutritional value for plant growth. Community service is a concrete manifestation of the role of academics in making a positive contribution to the development and safety of the surrounding environment. This activity not only aims to transfer useful knowledge and technology, but also encourages community independence in utilizing local potential that is often not optimally managed. One common problem encountered in many households is the high volume of wasted domestic waste, including rice washing water waste, which has long been considered worthless. This training provides a positive contribution to the community because it can be an alternative in finding alternative fertilizers to overcome fertilizer scarcity and prevent environmental pollution. This community service activity is a form of knowledge transfer from academics to the wider community to provide benefits based on the results of research that has been carried out on campus, especially the process of making liquid organic fertilizer.